DETERMINATION OF MINIMUM WAGES, GRDP AND INVESTMENT ON LABOR ABSORPTION IN THE AGRICULTURAL SECTOR FOR THE WEST OF ACEH PROVINCE - Manyamsari, Ira; Noratun Juliaviani; Nasution, Anisah (CV. Radja Publika, 2023)
The western region of Aceh Province is very famous for its abundant resources, especially in the agricultural sector. Almost half of the population in the western region of Aceh Province work in the agricultural sector. Provision of sufficient jobs in the agricultural sector will offset the addition of labor, so that unemployment in the western region of Aceh Province can be reduced. Thus, open unemployment will also be reduced and will improve the regional economy and the welfare of the people in the region.The research objective was to determine the effect of the minimum wage on employment in the agricultural sector and to determine the effect of investment on employment in the agricultural sector in the western region of Aceh Province. The analysis used in this research is multiple regression analysis using panel data. The result of this research is that the minimum wage has a negative effect on ISG. on employment absorption, while GRDP and investment have a positive and sig. on the absorption of labor in the agricultural sector in the western region of Aceh Province.